Dscam-mediated cell recognition regulates neural circuit formation. - Hattori, D.; Millard, S.S.; Wojtowicz, W.M.; Zipursky, S.L. (Annual Review of Cell and Developmental Biology, 2008)
The Dscam family of immunoglobulin cell surface proteins mediates recognition events between neurons that play an essential role in the establishment of neural circuits. The Drosophila Dscam1 locus encodes tens of thousands of cell surface proteins via alternative splicing. These isoforms exhibit exquisite isoform-specific binding in vitro that mediates homophilic repulsion in vivo. These properties provide the molecular basis for self-avoidance, an essential developmental mechanism that allows axonal and dendritic processes to uniformly cover their synaptic fields. In a mechanistically similar fashion, homophilic repulsion mediated by Drosophila Dscam2 prevents processes from the same class of cells from occupying overlapping synaptic fields through a process called tiling. Genetic studies in the mouse visual system support the view that vertebrate DSCAM also promotes both self-avoidance and tiling. By contrast, DSCAM and DSCAM-L promote layer-specific targeting in the chick visual system, presumably through promoting homophilic adhesion. The fly and mouse studies underscore the importance of homophilic repulsion in regulating neural circuit assembly, whereas the chick studies suggest that DSCAM proteins may mediate a variety of different recognition events during wiring in a context-dependent fashion.